Pearl's eight days of Chanukah - Zalben, Jane Breskin (Simon & Schuster Books for Young Readers, 1998)
Eight stories and activities during each night of Chanukah introduce the holiday and its practices. Includes descriptions of related recipes, crafts, songs, and games.